2021
DOI: 10.18231/j.ijceo.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

Five-year survey and management of sports-related eye injuries in Jakarta’s eye hospitals

Abstract: To examine the demographics and outcome of management in patients admitted with sports-related eye injuries in one of Jakarta's eye hospitals. Methods: Retrospective analysis 24 patients who admitted to a tertiary eye hospital in Jakarta with sportsrelated eye injuries between 2014 to 2019 was conducted. Standard descriptive statistical methods were used for analysis. Results: Out of 534 patients admitted to our hospital with ocular trauma between 2014 to 2019, 24 patients (4.5%) had sport-related eye injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
1
1
1
Order By: Relevance
“…Fishing could affect the eyes from the shhook, the lure striking the eye. 27 This current study noted that AC injury, including hyphema, was the most common clinical nding, which was similar to recent multicenter studies in Korea, 16 in the United States, 25 and Serbia. 13 Other common clinical ndings in this study included iris injury (iris prolapse and iridodialysis).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Fishing could affect the eyes from the shhook, the lure striking the eye. 27 This current study noted that AC injury, including hyphema, was the most common clinical nding, which was similar to recent multicenter studies in Korea, 16 in the United States, 25 and Serbia. 13 Other common clinical ndings in this study included iris injury (iris prolapse and iridodialysis).…”
Section: Discussionsupporting
confidence: 87%
“…This result was higher compared to other studies in Indonesia (16.7%), 25 and Finland (11%). 20 Primary globe repair was the most common performed surgical procedure in this study, while other studies reported lid repairs as the most common procedures.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation